A temática da sustentabilidade na área de recursos pesqueiros e na formação técnica em alimentos - Medeiros, Thatiane Brito da Silva (2020)
The rationality of modern thought, with the current patterns of development based on Western culture and with the economic globalization of the current times, has caused the rupture of the duality between man and nature. It is important to consider the urgent need of a paradigm shift with regard to the ecological, social and economic scope. Based on this vision, there is a greater awareness of the subject's responsibilities for the environment. The present research proposed in the first chapter to make a survey of the sustainable practices applied to the segments of the fishing activity, as well as analyzed the alternatives that favor the sustainable development of the sector, reflecting on suggestions, presented in the literature that integrate ecological benefits, economic and social. The study had as methodology a survey with investigation in bibliographic database. The literatures were analyzed, on three bases adopted. The search took place using theterms "Sustainable Practices + Fishing", "SustainablePractices + Aquaculture" and "Sustainable Practices + Fisheries Resources". Only 12 most relevant literatures in the approach of the theme met the criteria of this survey. Through the bibliographic survey, it was possible to identify three main categories of work developed in the periods between 2008 and 2019, the Environmental education, Management of natural resources, and Industry and sustainable practices. It appears that the studies on sustainability practices directed to the fishing sector are still very timid. The initiatives related to environmental sustainability addressed in the studies analyzed, are very relevant for the fishing sector, considering that the sector faces great difficulties in the environmental area. As for management measures, it is necessary that fisheries management to be built based on scientific and technological knowledge, so it is necessary to encourage research aiming to contribute to political decision-making with regard to environmental sustainability and the protection of aquatic biodiversity and water resources. The second chapter aimed to discuss the training of students in the Technical Course in Food of the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN), Campus Pau dos Ferros and the curricular proposals directed to the theme of sustainability, as well as its transversality in the practical context of the course formation. For the study an exploratory and descriptive research was carried out through field research. The data collect was performed using the questionnaire. As a result it was observed that some disciplines had direct and indirect approaches on the theme of environmental sustainability, especially on aspects related to the environmental issue. It was observed that the students have an environmental perception in with the environment is seen as a resource that needs to be managed, and not as nature or natural environment. Although this perception is focused on sustainability, it is also necessary to understand that this vision cannot be dissociated from the conception of the environment seen in the perspective of the collectivity, of the common good, where the environment must be seen as an integral part of the human collectivity, of the social environment that we are unique individuals with individualistic actions, but we are also part of the collective.